2015
DOI: 10.6007/ijarafms/v4-i4/1368
|View full text |Cite
|
Sign up to set email alerts
|

Testing Random Walk Behavior in the Damascus Securities Exchange

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The presence of Momentum effect in DSE market suggests that this market is inefficient of weak form of efficiency, which confirms the results of previous studies in this market such as Al-Ahmad (2012) and Abbas (2014).…”
Section: Discussionsupporting
confidence: 88%
“…The presence of Momentum effect in DSE market suggests that this market is inefficient of weak form of efficiency, which confirms the results of previous studies in this market such as Al-Ahmad (2012) and Abbas (2014).…”
Section: Discussionsupporting
confidence: 88%
“…They commented that ex-dividend price increased instead of decreasing in Dhaka Stock Exchange (DSE). The findings of Abbas (2014) shows that there is no leakage of information prior to announcement of dividend. As a result, significant abnormal returns before the dividend announcement date is also absent.…”
Section: Empirical Reviewmentioning
confidence: 89%
“…The study therefore concluded that the ASE stock market rejected the random walk hypothesis and was inefficient at the weak form level. Abbas (2014) examined whether daily stock returns on Damascus Securities Exchange follow a random walk for the period of 2009 to 2014. The study applied two parametric tests namely serialcorrelation test and variance ratio test, and two non -parametric tests, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%